Pengaruh Budget Ratcheting Terhadap Hubungan Antara Pendapatan Asli Daerah dan Belanja Daerah Pada Kabupaten/Kota di Wilayah III Cirebon - Neni Nurhayati (Jurnal Riset Keuangan dan Akuntansi, 2018)
This study aims to examine the effect of the Original Revenue on Regional Expenditure and examine the effect of Budget Ratcheting in moderating the influence of the Original Revenue on Regional Balanja. Tests on the effects of moderation and major effects by using regression analysis were done by tiered regression analysis method. There are two regression equations used, namely (1) by entering the main independent variable and moderating in one equation and then (2) adding a new independent variable in the form of the interaction of the two independent variables. Research subjects that serve as a place / location to conduct empirical studies are the Regional Financial and Asset Management Board and the Central Bureau of Statistics in: Kuningan District, Cirebon Regency, Cirebon City, Majalengka Regency and Indramayu Regency. This research is planned to be conducted for 6 (six) months, from April to September 2017. The results show that the original revenue influences regional expenditure and budget ratcheting effect on the relationship between the original revenue with regional spending.Keywords: Local Original Revenue, Regional Expenditure, Budget Ratcheting,